Mapping students' interest in a new domain: Connecting prior knowledge, interest, and self-efficacy with interesting tasks and a lasting desire to reengage. (October 2021) - Fryer, Luke K.; Shum, Alex; Lee, Ada; Lau, Peter
Abstract: How students experience educational environments and the interconnections between their readiness, task experiences and their long-term desire to reengage with course content are critical questions for educators. Research postgraduate students ( n  = 310) at a research-intensive university in Hong Kong, engaging in a 24-h introductory teaching course, participated in this study. Learner readiness for the course was assessed as prior Domain interest, self-efficacy, and knowledge. Subsequently, students completed four formative assessments, reported their on-task interest in seven strategically chosen tasks and end-of-course Course and Domain interest. Longitudinal-SEM tested interconnections between readiness components, Task, Course and Domain interest. Initial self-efficacy beliefs for teaching predicted early Task interest, while Domain interest was a predictor of Task interest in explicitly practical task experiences. Strong interconnections between Task interest across the study were evident. Individual written and social discussion tasks presented strong contributions to future Course/Domain interest. Implications for theory and practice are discussed. Highlights: This is a micro-analytic study integrating readiness, on-task interest and formative evaluation. Components of learner readiness have important and specific roles within on-task interest. Both directly and mediated, on-task interest is drivers of longer-term desires to reengage. Both task format and content are important components of a desire reengage.